Renewable Energy Communities as Examples of Civic and Citizen-Led Practices: A Comparative Analysis from Italy - Monica Musolino; Domenica Farinella (Land)
The analysis focuses on the practices of Italian renewable energy communities (RECs) which fall within the so-called civic energy sector, as well as citizen-led initiatives, which are widespread, especially in several regions of Southern Italy (Sicily, Sardinia, Campania), characterized by structural socioeconomic conditions of “lag” compared to the more economically developed North of the country. Added to these Southern areas is a richer region in the North (Trentino–Alto Adige) where, however, historical and institutional factors have allowed a wide diffusion and local rooting of collective initiatives for sharing energy from renewables. These initiatives started from the so-called historical cooperatives which still manage the production and distribution of energy derived mainly from hydroelectric plants. Our contribution intends to compare 10 case studies of RECs in relation to their organizational model through a qualitative study based on a set of in-depth interviews and socio-ethnographic observation. We used a complex theoretical lens combining different approaches, especially polycentric governance, multilevel perspective, and social acceptance theories. This framework is useful for focusing our analysis on the decentralization process related to the potential of RECs. The main results of our research concern the different effectiveness and speed of implementation in correlation with divergent structural and institutional conditions; the construction of different coalitions of actors in correspondence with socio-territorial differences, even within the same area of the country (the South); and the emergence of hybrid community energies (a mix of civic energy and citizen-led initiatives). The analysis shows that, despite a tendency towards institutional isomorphism, community energy practices are strongly influenced by local contexts. Moreover, they are significantly governed by a mutualistic and solidaristic logic, but also by strong internal mediation and guidance on the part of their promoters.